(untitled) (Revista Contexto & Educação, 2026)
This paper describes some of the results of a study focused on learning evaluation in Professional and Technological Education (VET). It seeks to analyze teachers’ conceptions of learning evaluation in VTE and the potential changes in understanding resulting from contact with an educational product for the development and application of evaluation instruments in a virtual teaching and learning environment. The study focused on the centrality of evaluation for the comprehensive development of students, particularly from an emancipatory perspective, which aims to develop critical, autonomous, and active individuals in the educational process. The research adopted a qualitative, applied approach with descriptive-explanatory objectives, using pedagogical intervention as its method. Data were collected through semi-structured interviews and analyzed through content analysis. The locus was a federal institute, and the subjects were eight Basic, Technical, and Technological Education (EBTT) teachers. This paper presents data from the first specific research objective: to identify teachers’ prior understanding and practices regarding learning evaluation in VTE. The results indicate evidence of a predominant appreciation for formative evaluation concepts, in which, in a sense, the teaching-learning process was already understood as continuous, dynamic, and guided by pedagogical mediation. Although some statements indicated the persistence of traditional practices focused on verification and measurement of results, these coexisted with discourses that emphasized monitoring, feedback, listening, and building bonds with students.